Kesuburan Tanah, Pertumbuhan dan Produktivitas Tanaman Kelapa Sawit (Elaeis guineensis) pada Tiga Kedalaman Mineral Pirit - Edy Sigit Sutarta; Dhimas Wiratmoko; Erwin Nyak Akoeb (Pusat Penelitian Kelapa Sawit, 2020)
Acid sulfidic land is one of the marginal land that has been used for oil palm development. Low soil acidity (pH) and high content of Al and Fe are limiting factors for oil palm development in this area. Oil palm yield in this area was very limited and could not reach the standard of oil palm productivity in mineral soils. The objectives of this study were mapping the pyritic depth distribution, and observing the soil fertility on three pyritic depth (40 – 60 cm, 60 - 90 cm, and >90 cm). The results of this study showed that Paya Rambe plantation had varied pyritic depths, between 40-110 cm. The shallow pyritic depth was found along the river to the sea estuary. Shallow pyritic depth soil has lower soil fertility than the deeper one. Soil with shallow pyritic layer has high acidity, Fe, S, and Al contents, also contain low macro nutrients (N, P, K, and Mg) availability. Furthermore, shallow pyritic depth reduced the oil palm growth, nutrients uptake and oil palm productivity.